Cultural Resilience in a Globalizing World: Centripetal Fortification and Centrifugal Innovation in Bali and Beishan - I Putu Permana Mahardika; I Gusti Ayu Gde Sosiowati; I Wayan Mulyawan; Holger Briel (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study investigates how Bali, Indonesia, and Beishan, China, strategically sustain their cultural identities amid globalising pressures. It addresses a gap in comparative resilience research by moving beyond sector-specific analyses to uncover the underlying principles of cultural adaptation. Using qualitative oral history, the research captures grassroots perspectives to reveal two contrasting paradigms: Bali enacts centripetal resilience, defending a sacred cultural core through ritual and social cohesion, whereas Beishan pursues centrifugal innovation, treating heritage as assets for entrepreneurial fusion with global culture. The findings demonstrate that the nature of perceived threats shapes whether communities adopt defensive fortification or proactive reinvention. The study argues that cultural resilience is not a universal strategy but a contextually coherent alignment of ontology, threat perception, and adaptive action. By proposing a comparative framework of centripetal and centrifugal resilience, it advances resilience theory and provides a transferable analytical lens for understanding how communities negotiate continuity and change across diverse cultural contexts.